Effect of wall-disruption on nutrient composition and in vitro digestion of camellia and lotus bee pollens - Yuan Yuan; Shun Zhong; Zeyuan Deng; Guangyan Li; Jinwu Zhang; Hongyan Li (Food Science and Human Wellness)
The nutrient digestion, absorption and biological activity of bee pollen may be limited due to the complex pollen wall. Here, the effect of superfine grinding technology on the release of nutrients from bee pollen were investigated, and their antioxidant activities and in vitro digestion were explored in this study. Results showed that the content of nutrients in bee pollen increased after wall disruption. Among them, fat content increased by 22.55%–8.31%, protein content increased by 0.54%–4.91%, starch content increased by 36.31%–48.64%, soluble sugar content increased by 20.57%–29.67%, total phenolic acid content increased by 11.73%–86.98% and total f lavonoids content increased by 14.29%–24.79%. At the same time, the antioxidant activity increased by 14.84%–46.00%. Furthermore, the active components such as phenolic compounds in the wall-disruption bee pollen were more readily to be released during the in vitro digestion, and easier to be absorbed because of their higher bioaccessibility. Antioxidant activities during in vitro digestion were also improved in wall-disruption bee pollen. These findings provide evidence that bee pollen wall disruption was suggested, thus, it is more conducive to exerting the value of bee pollen in functional foods.